Salicylic acid had the potential to enhance tolerance in horticultural crops against abiotic stress - Chen, Shanshan; Zhao, Chun-Bo; Ren, Rui-Min; Jiang, Jun-Hai (Frontiers in Plant Science, 2023)
Horticultural crops are greatly disturbed because of severe abiotic stress conditions. This is considered one of the major threats healthy life of the human population. Salicylic acid (SA) is famous as one of the multifunctional phytohormones that are widely found in plants. It is also an important bio-stimulator involved in the regulation of growth and developmental stages of horticultural crops. The productivity of horticultural crops has been improved with the supplemental use of SA even at a little amount. It had the good capability to reduce oxidative injury that occurs from the over-production of reactive oxygen species (ROS), potentially elevated photosynthesis, chlorophyll pigments, and stomatal regulation. Physiological and biochemical processes are revealing that SA enhances signaling molecules, oxidative, non-oxidative, osmolytes, and secondary metabolites activities within the cell compartments of plants. Numerous genomic approaches also explored that SA reconnoiters the transcriptional apprehensions, genomic expression, and metabolism of stress-related genes. Many plant biologists have been working on SA and it’s functioning in plants, however, its involvement in the enhancement of tolerance against abiotic stress in horticultural crops is still unidentified and needs huge attention. So, the current review is focusing on a detailed exploration of SA in physiological and biochemical processes in horticultural crops subjected to abiotic stress. Current information is more comprehensive and will be more supportive of the development of higher-yielding germplasm against abiotic stress.